2022
DOI: 10.1111/nph.18013
|View full text |Cite
|
Sign up to set email alerts
|

A structural homologue of the plant receptor D14 mediates responses to strigolactones in the fungal phytopathogen Cryphonectria parasitica

Abstract:  Strigolactones (SLs) are plant hormones and important signaling molecules required to promote the arbuscular mycorrhizal (AM) symbiosis. While in plants an /-hydrolase, DWARF14 (D14), was shown to act as a receptor that binds and cleaves SLs, the fungal receptor for SLs is unknown.  Since AM fungi are currently not genetically tractable, in this study, we used the fungal pathogen Cryphonectria parasitica for which gene deletion protocols exist, as a model, as we have previously shown that it responds to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Canonical SLs as 5DS (3), solanacyl acetate (23), and solanacol (22) in aqueous solutions were reported less stable than GR24 (56). [83][84] Generally, hydroxy-SLs with hydroxyl group on the A-or B-ring, such as strigol (1), orobanchol (10), and sorgomol (6), are less stable than non-hydroxy-SLs such as sorgolactone (5), 5DS (3), and solanacyl acetate (23). [17,[84][85] The low stability of noncanonical SL biosynthetic intermediates [e. g., CL (27), CLA (29), MeCLA (31), and derivatives] and noncanonical SLs [heliolactone (36), zealactone (41)] was also reported.…”
Section: Sls Analogs and Mimics Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Canonical SLs as 5DS (3), solanacyl acetate (23), and solanacol (22) in aqueous solutions were reported less stable than GR24 (56). [83][84] Generally, hydroxy-SLs with hydroxyl group on the A-or B-ring, such as strigol (1), orobanchol (10), and sorgomol (6), are less stable than non-hydroxy-SLs such as sorgolactone (5), 5DS (3), and solanacyl acetate (23). [17,[84][85] The low stability of noncanonical SL biosynthetic intermediates [e. g., CL (27), CLA (29), MeCLA (31), and derivatives] and noncanonical SLs [heliolactone (36), zealactone (41)] was also reported.…”
Section: Sls Analogs and Mimics Stabilitymentioning
confidence: 99%
“…SLs have been also found active on phytopathogenic fungi. [6] SLs were identified in 2008 as the ninth class of hormones, initially discovered for the control of aerial plant architecture. [7] The discovery of a new class of hormones such as SLs is a major advance in plant biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in structure could induce a variation in the receptor-SL mimic affinity as well as variations in the conformational changes, which could explain the heterogeneity in the biological outcome observed. Recently, a fungal homolog from Cryphonectria parasitica, of the plant DWARF14 (D14) SL receptor, was reported and characterized [90]. This receptor is able to hydrolyze GR24 and this enzymatic activity requires the known catalytic triad Ser/His/Asp.…”
Section: Biological Activity Of Synthesized Compoundsmentioning
confidence: 99%
“…D14 receptors include members that have undergone wide differentiation in plants and beyond. A recent study found a D14‐like protein in the phytopathogen Cryphonectria parasitica that interacts with strigolactones, hydrolyses them and is needed for their perception, even though the ecological significance of strigolactones for this organism is unresolved (Fiorilli et al, 2022 ). Also the perception of strigolactones as germination stimulants in seeds of parasitic plants relies on an expanded family of D14‐like receptors, called HYPOSENSITIVE TO LIGHT (HTL).…”
Section: Latest Developments In the Synthesis Perception And Transpor...mentioning
confidence: 99%